เมทิเลชันของยีน CCNA1 ในเซลล์สายพันธุ์มะเร็งปากมดลูกที่ถูกทรานสเฟกต์ด้วยยีน E7 ของ Human Papillomavirus ไทป์ 16 - วัชรพงศ์ ภักดีชายแดน (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The main cause of cervical cancer are infection of human papillomavirus (HPV) by which high-risk HPV (HR-HPV) can be detected in cervical cancer patients more than 90%, particularly HPV type 16 and 18. Previous studies found the correlation of methylation and expression inhibition of genes leading to cancer and cervical cancer which is infected by HPV is associated with methylation of CCNA1 which has a role as tumor suppressor gene in cervical cancer up to 93%. The aim of this research to study the correlation of E7 gene in HPV type 16 and DNA methylation on CCNA1 promoter. We cultured 3 cervical cancer cell lines : HeLa (HPV type 18 infection), SiHa (HPV type 16 infection) and C33A (no HPV infection) and 3 head and neck cell lines : HN4, HN12 and HN17 which are still unknown of HPV type infection. We detected HPV type infection in these 6 cell lines and methylation and expression of CCNA1. Then we emphasized to study E7 gene of HPV type 16 by constructing the plasmid inserted E7 gene of HPV type 16 and trasfecting it into C33A and HN12. Lastly, we verified the difference of methylation status and expression of CCNA1 in these 2 transfected cell lines and non-transfected cell lines.The results show that C33A which is transfected by E7 gene of HPV type 16 has more methylation on CCNA1 promoter as well as the expression of CCNA1 is decreased when compared to non-tranfected cells. What’s more, HN12 which is transfected by E7 has methylation; yet methylation is not found in non-tranfected HN12. Besides that the decreasing expression of CCNA1 is found. On the whole, we conclude that E7 gene of HPV type 16 has affected to methylation of CCNA1 in cervical cancer.